Pemilihan Kawasan Wisata Kuliner sebagai Daya Tarik Wisata di Kota Bogor - Clara Mutiara; Riza Firmansyah (Journal of Tourism Destination and Attraction, 2018)
Bogor Barat Culinary Area is a culinary area with the most restaurants in the cityof Bogor. It can be known that currently there are approximately 65 restaurants in North Bogor. This area is quite strategic and islocated on the trade route that has been planned by the Bogor City Government, this is the big opportunity for North Bogor Region as the biggestculinary area in th ecity of Bogor. In this study the concept of culinary tourism was used to analyze several restaurants with the concept of culinary tourism seen from the Menu, Food Production Strategy, Service, Price and Room Decor / Atmosphere by taking a sample of 10 restaurants in North Bogor, including : Ayam Geprek Istimewa, Bakso Misterius, Bumi Aki, Foresthree Resto, Gurih 7, Lemongrass Resto, Teras Dara, Whatever Resto dan Warung Urban.The purpose of this study is to analyze the existing conditions of culinary tourism in North Bogor and analyze the selection of restaurants in North Bogor. The design of this study uses a descriptive approach with qualitative methods. For the selection of culinary tourism area, it uses AHP analysis to find out which culinary tourism concept is more desirable and what restaurant is the priority. To find out the development strategy of North Bogor culinary area with a SWOT analysis.